Creating A Green Economic Ecosystem Through Lean Canvas Model: BIPV System Achieving Net Zero Emission - Susan; Eric Harianto; Christian Anggrianto; Dyah Kusuma Wardhani; Yusuf Ariyanto (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
Green Economy is a sustainable economic activity to be able to improve people's welfare without neglecting the impact that causes damage to the environment. This concept prioritizes economic activities with low carbon emissions. Currently, the largest carbon emissions are caused by power plants that still use non-renewable natural resources. One of the efforts made to reduce carbon emissions is to use a solar power plant, known as PV Solarcell. However, with new developments and discoveries for solar power plants, BIPV is perfected. BIPV is a solar power plant where the existing solar panels are attached to buildings or buildings. The aim of this research is to be able to create a new green economy business model for BIPV power plants by using lean canvas tools. This research uses descriptive qualitative method. This research starts from May to October 2022. The results of this study using the lean canvas concept can create an integrated and sustainable green economy business model ecosystem to be able to create new value.